Perancangan Sistem Integrasi Aplikasi Terdistribusi Pada Transaksi Data Pesanan Menggunakan Web Service - Nasir Suruali (Industrial Engineering Study Program, Pattimura University, 2015)
Order data is the main need in supply chain management in a company in order to achieve a smooth flow of data in the company's management. The main problem that arises is the data flow of orders that are not controlled, the production process that is not appropriate lead time, inventory and location of waste that are at a distance apart. Another factor that emerged was the limited mechanisms of integration of applications and interoperability between systems. The development of the Internet as a medium of communication in e-business is one chance in doing integration among these applications. One of the technologies developed at this time and is intended to accommodate diversity and that problem is the Web Service. At the writing of this article, to design and Web Service system in the case within the enterprise application integration between the marketing with production parts. Implementation of Web Service performed include transaction processing and tracking orders data. The design is done using UML models and implementations using software from Microsoft's .NET platform. Results of research conducted indicates that the Web Service is a technology that deserves to efficiency and effectiveness in a garment company.